Physical Qualities of An Athlete As A Subject Of Education At The Initial Stage Of Sports Training (Eurasian Journal of Learning and Academic Teaching, 2024)
This article, which is presented, provides information on the general basics of general and special physical training of table tennis players and its development. Also, the importance of general and special physical training in improving the level of physical fitness of table tennis players is highlighted.